Analisis Perencanaan Obat Berdasarkan Metode ABC Indeks Kritis di Instalasi Farmasi Rumah Sakit Umum Daerah Ciawi - Widodo, Irwan Unggul; Pujianto, Pujianto (UI Scholars Hub, 2020)
Pharmacy unit has important role to determine service quality in hospital. For supporting patients service, Ciawi Region Public Hospital used drugs based on national formulatorium which is contain 1.176 kind of drugs with investation value Rp. 17.315.126.250,-. Ciawi Region Public Hospital already became National Health Coverage provider since 2014 with 74,04% the Indonesian National Healthcare Insurance (BPJS) patients and getting increase everyday. The big investation and amount of drugs need to supervise for accurate drugs support and getting effectivity and eficiency. Consumption method which already used by Ciawi Region Public Hospital is not fulfillt he drugs demand yet, still making drugs stock out and stock over. This is an analytic research to see the description of drugs need planning in Ciawi Region Public Hospital, with qualitative and quantitative approach. This research including deep interview, observation, document study and ABC method counting analysis for drug using, ABC investation method anlysis and ABC critical index method from Grup A (using) and Grup A (investation). The research also doing moving average forecasting method for 4 months period for Grup A, critical indeks ABC analysis in 2018 and counting amount of drugs order (EOQ), order frequency, Safety Stock (SS) and repeat order point (ROP). ABC method counting analysis for drug using showed that Grup C has 990 items (84,18%) slow moving type. ABC critical index method from Grup A showed 45 items with investation value Rp. 5.876.003.324,- and Grup B has 100 items with investation value Rp. 9.147.434.944,-. The Grup A and B investation cost is very high and need to plan and controll with EOQ, SS and ROP counting methods. EOQ will produce smallest total cost that will give efficient result. Ciawi Region Public Hospital is expected to make drugs supporting plan with quality controll and cost efficiency. The hospital also expected for having drugs amount order counting, safety stock and repeat order point.